THE DISENGAGEMENT FROM DIVERSITY MANAGEMENT IN THE LAST PERIOD OF OTTOMAN WORKFORCE: ALIENATION (Third Sector Social Economic Review, 2016)
The Ottoman Empire with the multi cultural structure of language, religion and race managed all the values and people efficiently for centuries. Though diversity management took place in the literature by emerging efforts of America in 1990s, before that time this model had been practiced successfully. But with the internal and external factors in the last period of Empire, The State started to lose its efficient position. In this study, diversity management in the last period of work force has been considered in details. Then with the experiment of foreign and non-müslim alienation issue have been under discussion.
Keywords: Diversity Management; Workforce in the Ottoman; Alienation